Mempererat Hubungan Rumah Tangga di Tengah Gejolak Kehidupan Modern Melalui Pendidikan Keluarga - Juwinner Dedy Kasingku; Lauda Woy Lauda Woy (Journal of Innovative and Creativity, 2025)
Family is an important place for a person’s development, where we learn about love, togetherness, and support. However, the challenges of modern life, such as busy work schedules and technological advancements, can affect family harmony, especially in communication. This study aims to understand how to maintain family integrity amid the rising issues of divorce. The research uses a qualitative method by analyzing various related articles. The results show that factors such as a lack of responsibility, economic problems, and domestic violence can harm family unity. To maintain harmony, it is crucial for families to communicate well, forgive each other, and pray together. These steps can strengthen family relationships, create a safe environment, and provide a healthy atmosphere for children. In conclusion, maintaining family integrity requires joint effort, focusing on good communication, love, and togetherness in prayer to prevent divorce and create a harmonious family.